Rhamnus liboensis, a replacement name for Rhamnus calcicola Q. H. Chen (Rhamnaceae) - Deng, Yunfei (Phytotaxa, 2012)
Rhamnus Linnaeus (1753: 193) is the largest genus of Rhamnaceae. It consists of about 150 species distributed in temperate to tropical regions of the Northern hemisphere, mainly in E Asia and North America, and a few species in Europe and Africa (Madan & Schirarend 2004, Mabberley 2008). Fifty-seven species are currently recognized in China (Chen & Schirarend 2007).